Unaddressed Cultural Nexus: Phenomenological Inquiry into Past Life Regression at Pasar Kinanti for Identity Formation and Future Wisdom - Rizki Firmansyah; Azka Prasetyo; Khilda Rahma Alifia (Universitas Galuh, 2026)
This study examines Past Life Regression (PLR) as a socio-cultural and symbolic practice in Pasar Kinanti, a community-based traditional market in Indonesia. PLR is not treated as a metaphysical claim but as symbolic memory and narrative experience shaping identity and future orientation. Using a qualitative phenomenological approach, data were collected through in-depth interviews with 12 participants, participant observation, and analysis of community digital documentation. Data were analyzed using interpretative phenomenological thematic analysis based on van Manen’s framework. Four themes emerged: (1) PLR as a symbolic and embodied reflective experience, (2) identity construction through cultural and spiritual narratives, (3) production of future wisdom as moral and social guidance, and (4) negotiation between spiritual meaning and digital commodification. The findings show that Pasar Kinanti functions as an experiential cultural space where symbolic memory and collective imagination are produced. However, tensions arise between authenticity, representation, and digital commodification. This study contributes to phenomenological research on public space and to debates on digital cultural economy by highlighting the ambivalence between meaning-making and symbolic commodification